The Referential Function Used in L’oreal Paris Advertisements - Widiadnya Putri, I Gusti Ayu Vina; Ardiantari, Ida Ayu Putri Gita; Sutariani, Ni Made (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2022)
This study focused on analyzing language function, especially referential function. This function used in many kinds of communication, including in daily communication. Therefore, this study aimed to analyze the referential function as well as its elements in L’Oreal Paris advertisements. In regards to the aims of the study, two theories were applied. The theory proposed by Jakobson (1980: 82) was used to analyzed referential function used in the transcripts of 19 advertisements videos of L’Oreal Paris. In addition, the theory proposed by Quirk and Greenbaum (1973: 12) was used to analyze the sentence elements of that function found in the transcripts of L’Oreal Paris advertisements videos. Observation method with watching and note taking technique were applied in collecting the data. Descriptive qualitative method was applied in analyzing the data. The data were presented by formal and informal methods. There were 42 referential functions found in the transcripts of 19 advertisements videos of L’Oreal Paris. Those data were presented by various elements of sentence. However, some of the referential functions found were non-sentences.